Dampak Platform Daring Terhadap Motivasi Belajar Mahasiswa - Syata, Wahyu Muh (INDO PUBLISHING, 2025)
The digital revolution has transformed the landscape of higher education, particularly thru the implementation of online learning platforms. This study aims to analyze the impact of using online learning platforms on student learning motivation in higher education. Using a qualitative literature review method, this study integrates the results of various previous studies to understand the dynamics of the relationship between online learning platforms and student learning motivation. The research results indicate that online learning platforms have a dual impact on learning motivation. On the one hand, platforms with motivational features such as credit systems, gamification, and quick feedback can increase student engagement and intrinsic motivation. On the other hand, various challenges such as monotonous materials, limited direct interaction, internet connectivity issues, and a lack of social support can decrease student learning motivation. This study concludes that the effectiveness of online learning in increasing motivation depends on four key elements: (1) students' readiness in digital literacy and self-regulation skills, (2) adequate access to technology and infrastructure, (3) social support from family, peers, and lecturers, and (4) student-centered pedagogical design with engaging features. Online learning can be an effective alternative and a catalyst for improving motivation and learning outcomes if implemented with an approach that considers the balance between technological, social, and psychological aspects